2018
DOI: 10.1111/ejh.13105
|View full text |Cite
|
Sign up to set email alerts
|

Off‐label use of 4‐factor prothrombin complex concentrate is common despite little known benefit: A retrospective study

Abstract: Off-label use of 4F-PCC is likely common, occurring in nearly 40% of drug administrations at our center. Larger-scale prospective trials studying specific indications are needed for validation in off-label settings. Until such evidence is available, given potential harms historically displayed by off-label use of other hemostatic agents, limiting off-label 4F-PCC use is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 17 publications
3
18
0
1
Order By: Relevance
“…Our study also provides insight into the financial costs of 4F-PCC for both on-and off-label reasons. Interestingly, Scharman et al 23 noted that there was no difference in thromboembolic events, which our study could not evaluate accurately. Despite these differences, the conclusions from both studies support the finding that patients receiving 4F-PCC for off-label reasons have a higher in-hospital mortality rate.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Our study also provides insight into the financial costs of 4F-PCC for both on-and off-label reasons. Interestingly, Scharman et al 23 noted that there was no difference in thromboembolic events, which our study could not evaluate accurately. Despite these differences, the conclusions from both studies support the finding that patients receiving 4F-PCC for off-label reasons have a higher in-hospital mortality rate.…”
Section: Discussionmentioning
confidence: 56%
“…To our knowledge, the only previous report of a direct comparison between on-versus off-label 4F-PCC use is by Scharman et al, 23 who evaluated 154 patients receiving 4F-PCC at a single institution. Similar to our findings, they found that patients receiving 4F-PCC for off-label reasons had a twofold higher in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difficulty in achieving therapeutic activated clotting time in these three patients. Median intensive care unit stay among all 11 patients was 2 [1-3] days and median hospitalization duration was 5 [2][3][4][5][6][7] days. No deaths occurred before discharge.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Os concentrados de complexo protrombínico possuem um papel bem estabelecido e investigado por ensaios clínicos randomizados para reversão rápida da anticoagulação com antagonista da vitamina K, com estudos comprovando redução da mortalidade, correção rápida do INR e sem aumento do risco de eventos tromboembólicos (Arachchillage et al, 2019;Margraf et al, 2022). No entanto, seu uso off-label aumentou expressivamente, alguns autores relataram até 40% das vezes, já numa coorte retrospectiva, a utilização off-label do CCP de 4 fatores (CCP-4) ocorreu em 76% dos pacientes tratados (Scharman et al, 2018;Roberts et al, 2021). Estas indicações ausentes na bula incluem principalmente a reversão da coagulopatia induzida pelos novos anticoagulantes orais diretos, tratamento ou profilaxia de sangramento de deficiências congênitas dos outros fatores da coagulação dependentes de vitamina K, pré-operatório para diminuir o sangramento em pacientes que não tomam anticoagulantes orais ou em um cenário de trauma com transfusões maciças (Nesek Adam & Bošan-Kilibarda, 2022).…”
Section: Discussão Composições Existentes E Indicações On-label E Off...unclassified